The Concise History of the Theological Journal “Polonia Sacra” - Henryk Sławiński (Polonia Sacra)
The paper deals with the history of the theological journal of Theological Faculty in Krakow. It was initiated just before the end of the First World War, in 1918, and published not without difficulties. There were only three issues printed till the Second World War. After it the publication of “Polonia Sacra” was reinitiated in Krakow. However, because the communist government in Poland expelled the Theological Faculty from Jagiellonian University in Krakow, and allowed only that the theology might be taught at the Academy of Catholic Theology in Warsaw, the journal “Polonia Sacra” was published for a very short time in Warsaw. The renewal of the journal “Polonia Sacra” as the official publication of the Faculty of Theology in Krakow was restarted again in 1997 and has been continued till now. The Internet era became a challenge for the journal, which gained the national recognition, and has the aspiration to be an international forum for the academic exchange of theological research.